Excel PivotTables and PivotCharts : your visual blueprint for creating dynamic spreadsheets - McFedries, Paul (Visual blueprint., 2010)
Master two of the most powerful features of Excel Even if you use Excel all the time, you may not be up to speed on two of Excel's most useful features. PivotTable and PivotChart turn long lists of unreadable data into dynamic, easy-to-read tables and charts that highlight the information you need most; you can tweak results with a click or easily fuse data from several sources into one document. Now you can learn how to tap these powerful Excel tools with this practical guide. Using a series of step-by-step tutorials and easy-to-follow screenshots, this book shows you in a v.